Intention to reuse Gojek Application: The parallel mediating role of attitude and satisfaction toward application using AMOS-SEM approach - Sudibyo, Zsaghandy Adjisuastika; Hudayah, Syarifah; Indriastuti, Herning (Privietlab, 2025)
This study examines the influence of perceived usefulness and ease of use of the Gojek application and the intention to reuse the application with mediated attitudes and user satisfaction among Millennials and Generation Z. The focus of this research is on the big cities of East Kalimantan, Indonesia, namely Samarinda and Balikpapan. Data were extracted from 128 respondents using snowball sampling, and the analysis was conducted using AMOS structural equation Modelling. The findings show that perceived usefulness significantly affects the attitude and satisfaction of Gojek application users but has no significant effect on the intention to reuse application users. Perceived ease of use had an insignificant effect on attitudes, satisfaction, and intention to reuse Gojek application users. There is only one significant relationship between indirect variables; perceived usefulness has a significant effect on intention to reuse the application through the attitude toward the application. However, the other indirect relationships had an insignificant effect. This finding highlights the importance of perceived usefulness for Gojek application users. Although consumers admit to using an application based on attitude and satisfaction, they are reluctant to reuse the application because many competitors offer promotions and lower prices, so consumers feel they have a choice. Tests before the full AMOS model using confirmatory factor analysis for exogenous and endogenous factors showed significant results for all relationships between variables.